Strategi Komunikasi Pemasaran Pengelola Nama Domain Indonesia (pandi) Registry Nama Domain Tingkat Atas Indonesia - Yasin, Rayhan Muhammad; Anggraeni, Clara Novita (eProceedings of Management, 2024)
Currently, people use internet devices not only for communication but also for buying and selling activies carried outby traders and consumers. Buying and selling transactions carried out between traders and consumers are veryefficient. This is very profitable for traders because business can be done without renting accommodation. By utilizingthe interney, traders can create their sites, which are called website. The website itself is a document written inHypertex markup language format and accessed via HTTP to transfer information from the web server so that it canbe displayed to users via a web browser in static form. In Indonesia, there is an institution that manages the use ofIndonesia’s website domain. PANDI (Indonesia Domain Name Manager) has the authority the formulate policies andcreate .id domains in Indonesia. The Use of domain names in Indonesia Is currently still dominated by .com. PANDI’srole is to transfer the use of the .com domain name to .co.id so that the Indonesian indentity is present on the website.Because people are more familiar with the .com domain, PANDI face the challenge of attracting people’s attention tocreate a domain on PANDI. To increase sales of .id products in Indonesia, a good marketing communication strategyis needed. The research method use in this research is qualitative with a post-positivism approach by conductinginterviews. The research results show that PANDI use a marketing communication strategy consisting of 7 strategies.Of the 7 strategies, PANDI only uses 5 strategies, namely sales promotion, personal selling, Sponsorship, andadvertising, while the other 2 are not. In marketing domain products, PANDI only acts as a formulator and sellsproducts through the registrar. Keywords-buying and selling transactions, website, PANDI, marketing communication strategy.